Future Prospects for Islamic Political Parties in Indonesia's Democratic Contestation after the 2024 General Elections - Nastain, M; Huda, Muhammad Chairul; Nugroho, Catur; Habibi, Burhan Yusuf (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research analyzes the prospects of Islamic political parties in Indonesia's democratic contestation after the 2024 elections. Islamic political parties have never been able to compete with nationalist parties in the last four elections. The dominance of nationalist parties is shown in parliamentary contestation and in the presidential and vice-presidential elections, making Islamic parties have no logical choice but to join the coalition of nationalist parties. The future of Islamic political parties has become a polemic because they see their position increasingly squeezed by the strengthening of nationalist parties. This research was conducted using a literature study approach by collecting primary and secondary data from the official government website and supported by secondary data from various media channels such as detik.com and cnbc.com. Data collection begins with field observations to find preliminary data to guide further data collection. The results show that Islamic political parties still have potential prospects if they can optimize several factors, including the demographics of Muslims in Indonesia, Islamic militancy, the close relationship between the ideology of mass organizations and political parties, and public expectations. .